Students' responses to "The Gift of the Magi" and imaginative re-creations - Muhammad Rifqi; Januarius Mujiyanto; Rudi Hartono; Sri Wuli Fitriati (Indonesian Journal of Applied Linguistics, 2022)
Research has thus far shown that students' interest and active involvement are pivotal in the language learning process. However, there is a paucity of research examining how an English literary text can be exploited to bolster student engagement in an Indonesian EFL setting. Occupying this niche, this article focuses on the student's responses and the application of imaginative re-creation to the short story ("The Gift of the Magi"). Twenty-eight 3rd-semester English students taking the "Basic Reading Comprehension" course at a private university in Semarang (Indonesia) participated in this study. Couched under the reader-response theory, the students were asked to imaginatively recreate meanings after they read the text. The results showed that the students were actively involved and responded to the text during the learning process in various ways. Several students' responses were still very close to the original text, while the others were fairly different from the original. Throughout the learning process, the students actively interacted with texts and engaged with other learners. These interactions help to create a relaxing environment for the learners, which aids comprehension and encourages creativity in the creation of a new text. These findings shed light on the further development of students' creative writing in EFL teaching.